COVID-19 in Children With Cancer: A Single Low-Middle Income Center Experience. Issue 8 (7th November 2021) - Ebeid, Fatma S.E.; Ragab, Iman A.; Elsherif, Nayera H.K.; Makkeyah, Sara; Mostafa, Salwa; Eltonbary, Khadiga; Matbouly, Safa; Mostafa, Aya; Goma, Heba; Agwa, Sara H.; Hafez, Hala M.; Girgis, Samia; et al.
Abstract : Background: Coronavirus disease-2019 (COVID-19) could be associated with morbidity and mortality in immunocompromised children. Objective: The objective of this study was to measure the frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among hospitalized children with cancer and to detect the associated clinical manifestations and outcomes. Methodology: A prospective noninterventional study including all hospitalized children with cancer conducted between mid-April and mid-June 2020 in Ain Shams University Hospital, Egypt. Clinical, laboratory, and radiologic data were collected. SARS-CoV-2 infection was diagnosed by reverse transcription polymerase chain reaction tests in nasopharyngeal swabs. Results: Fifteen of 61 hospitalized children with cancer were diagnosed with SARS-CoV-2. Their mean age was 8.3±3.5 years. Initially, 10 (66.7%) were asymptomatic and 5 (33.3%) were symptomatic with fever and/or cough. Baseline laboratory tests other than SARS-CoV-2 reverse transcription polymerase chain reaction were not diagnostic; the mean absolute lymphocyte count was 8.7±2.4×10 9 /L. C-reactive protein was mildly elevated in most of the patients. Imaging was performed in 10 (66.7%) patients with significant radiologic findings detected in 4 (40%) patients. Treatment was mainly supportive with antibiotics as per the febrile neutropenia protocol and local Children Hospital guidance for management of COVID-19 in children. Conclusions: Pediatric cancer patients with COVID-19 were mainly asymptomatic or with mild symptoms. A high index of suspicion and regular screening with nasopharyngeal swab in asymptomatic hospitalized cancer patients is recommended.